186k views
5 votes
What are the factors of m2 – 6m + 6m – 36? (m – 2)(m + 18) (m – 3)(m + 3) (m – 4)(m + 9) (m – 6)(m + 6)

2 Answers

4 votes
(m – 6)(m + 6) is the answer.
If you distribute them, you'll get m^2 - 36
User MaximeKan
by
5.2k points
4 votes

Answer:


(m-6)(m+6)

Explanation:

we have


m^(2) -6m+6m-36

Simplify


m^(2) -6m+6m-36=m^(2) -36

we know that

In a difference of square


(a^(2)-b^(2))=(a+b)(a-b)

Remember that


36=6^(2)

therefore


(m^(2)-6^(2))=(m+6)(m-6)


User Ivan Vergiliev
by
6.0k points